A stable solid oxide fuel cell cathode material achieved by A-site regulation and its preparation and application

Through the A-position cation regulation of cobalt-based bisperovskite material, Ba1-xGd0.8Pr0.2+xCo2O6-δ cathode material was prepared, which solved the problem of slow oxygen reduction reaction kinetics in the medium temperature range of SOFCs cathode material, achieved high electrocatalytic activity and stability, and improved battery performance.

CN114744222BActive Publication Date: 2025-02-25SOUTH CHINA UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210433065.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-22
Publication Date
2025-02-25
Estimated Expiration
2042-04-22

AI Technical Summary

Technical Problem

The kinetics of the cathode materials of existing solid oxide fuel cells (SOFCs) in the medium temperature range are slow, resulting in a degradation of battery performance and insufficient stability and activity of the material.

Method used

By regulating the A-position cation of the cobalt-based bisperovskite material AA’Co2O6-δ, a cathode material Ba1-xGd0.8Pr0.2+xCo2O6-δ (0≤x≤0.4) was prepared to improve its electrochemical performance and durability.

Benefits of technology

A cathode material with high electrocatalytic activity for oxygen reduction reaction in the medium temperature range of 600-800°C is achieved, which significantly improves the polarization impedance, output power and stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003610354120000011
    Figure HDA0003610354120000011
  • Figure HDA0003610354120000012
    Figure HDA0003610354120000012
  • Figure HDA0003610354120000021
    Figure HDA0003610354120000021
Patent Text Reader

Abstract

The present invention belongs to the technical field of solid oxide fuel cells, and discloses a stable solid oxide fuel cell cathode material realized by A-position regulation and its preparation and application. The cathode material is characterized in that: its composition formula is AA'B 2 O 6‑δ The specific molecular formula is Ba 1‑x G 0.8 Pr 0.2+x Co 2 O 6‑δ , wherein 0≤δ≤1, δ is the oxygen vacancy content; x satisfies: 0≤x≤0.4. The present invention also discloses a method for preparing a cathode material. The anion material of the present invention has high electronic conductivity, low polarization impedance, low activation energy, high power density and good stability. The cathode material of the present invention is used in a fuel cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid oxide fuel cells, and in particular relates to a stable solid oxide fuel cell cathode material realized by A-site regulation, and a preparation method and application thereof. Background Art

[0002] Solid Oxide Fuel Cells (SOFCs) are energy storage and conversion devices that can directly convert chemical energy stored in fuel (mainly hydrogen and hydrocarbons) and oxidants into electrical energy without being restricted by the Carnot cycle. They have the characteristics of high energy conversion efficiency, no pollutant emissions, and environmental friendliness. The main structure of SOFCs includes a dense electrolyte layer, a porous cathode layer, and an anode layer. At present, perovskite materials are widely used as cathode materials for SOFCs because of their characteristics of both oxygen ion conduction and electron conduction. However, since SOFCs often need to operate under high temperature, high water vapor content, and polluted air conditions, high requirements are placed on the stability and activity of cathode materials. Reducing the operating temperature of SOFCs from a high temperature of 1000°C to a medium temperature range of 800°C or lower can not only improve the structural stability of the system, but also use cheaper materials, thereby reducing the overall cost. However, the temperature reduction will also cause the kinetic process of the oxygen reduction reaction (ORR) associated with the cathode to become significantly slower, resulting in a significant increase in the area specific resistance or interface resistance of the battery and a decrease in battery performance. Therefore, it is of great significance to develop a strong perovskite cathode material / structure with high electrocatalytic activity for ORR in the medium temperature range of 600-800℃.

[0003] Double perovskite AA'B2O 6-δ It is a derivative structure of perovskite materials. The A-site and A'-site cations are arranged alternately along the c-axis to form an ordered layered structure. This ordered layered structure can provide a unique channel for the transport of oxygen ions. At the same time, it can reduce the binding ability of rare earth elements and oxygen at the A-site, which is conducive to the conduction of oxygen ions and can significantly improve the ORR activity of the cathode. Among them, the cobalt-based double perovskite material AA'Co2O 6-δ It has high electrical conductivity and oxygen reduction catalytic activity. By further regulating the A-site elements of cobalt-based double perovskite oxides, such as element doping and introduction of defects, its electrochemical performance and durability as cathode materials for SOFCs can be further improved. Summary of the invention

[0004] In order to overcome the shortcomings and deficiencies of the prior art, the purpose of the present invention is to provide a stable solid oxide fuel cell cathode material and a preparation method thereof by regulating the A position. 6-δ ) was regulated by the A-position cation to prepare Ba 1-x G 0.8 Pr 0.2+x Co2O 6-δ (0≤x≤0.4) cathode material. By regulating the A position of the material, the electrochemical performance and durability of the material as the cathode material of SOFCs are improved.

[0005] Another object of the present invention is to provide an application of the cathode material. The cathode material is used in a solid oxide fuel cell.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] A stable solid oxide fuel cell cathode material achieved by A-position regulation, the general formula of which is AA'B2O 6-δ The specific molecular formula is Ba 1-x G 0.8 Pr 0.2+x Co2O 6-δ , where 0≤δ≤1, δ is the oxygen vacancy content.

[0008] The x satisfies: 0≤x≤0.4, preferably x=0.2.

[0009] When x=0.2, the molecular formula of the solid oxide fuel cell cathode material is: Ba 0.8 G 0.8 Pr 0.4 Co2O 6-δ .

[0010] The preparation method of the above-mentioned solid oxide fuel cell cathode material includes the following steps: Ba(NO3)2, Gd(NO3)3·6H2O, Pr(NO3)3·6H2O, and Co(NO3)2·6H2O are prepared by solution combustion method according to the stoichiometric ratio of the molecular formula.

[0011] Specifically, the process includes the following steps: uniformly mixing Ba(NO3)2, Gd(NO3)3·6H2O, Pr(NO3)3·6H2O, and Co(NO3)2·6H2O in water; adding glycine and citric acid monohydrate to form a mixed solution; heating and stirring at a constant temperature until the water evaporates to form a gel-like substance; heating the gel-like substance until it is completely burned to obtain a fluffy cathode material precursor powder; and calcining the precursor powder to obtain the desired cathode material.

[0012] The molar ratio of the total metal ions of Ba, Gd, Pr, and Co: glycine: citric acid monohydrate is (3.5-4.5): (2.5-3.5): (2.5-3.5).

[0013] The temperature of the constant temperature heating and stirring is 80-130°C.

[0014] The gelatinous substance is heated to complete combustion means that the gelatinous substance is kept at 250-300° C. for 5-10 hours.

[0015] The calcination temperature is 900-1000° C., and the calcination time is 2-5 hours.

[0016] Application of the solid oxide fuel cell cathode material in a fuel cell.

[0017] The application is as a cathode in an oxygen ion conducting solid oxide fuel cell.

[0018] The oxygen ion conducting solid oxide fuel cell comprises, from bottom to top, an anode, a transition layer, an electrolyte, and a cathode. The cathode is the solid oxide fuel cell cathode material.

[0019] The electrolyte is La 0.8 Sr 0.2 Ga 0.8 Mg 0.2 O 3-δ (LSGM).

[0020] The transition layer is La 0.4 Ce 0.6 O 2-δ (LDC).

[0021] The anode is NiO and Gd 0.1 Ce 0.9 O 2-δ (GDC) is a composite anode composed of a mass ratio of 6-7:4-3.

[0022] The present invention evaluates the electrochemical performance of the cathode material. The cathode material of the present invention has high conductivity, output power and battery stability.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The present invention relates to a high-performance solid oxide fuel cell cathode material (such as Ba 0.8 G 0.8 Pr 0.4 Co2O 6-δ(BGPC) is prepared by solution combustion method and has low polarization impedance, low activation energy, high power density and good stability. For example, the polarization impedance of the symmetrical battery BGPC|LSGM|BGPC at 800℃, 750℃, 700℃, 650℃, and 600℃ is 0.020Ωcm 2 ,0.037Ωcm 2 ,0.077Ωcm 2 ,0.185Ωcm 2 and 0.509Ωcm 2 The activation energy is 1.31 eV. The output power of the single cell Ni-GDC|LDC|LSGM|BGPC supported by LSGM electrolyte can reach 1.189 W cm at 800℃, 750℃, and 700℃, respectively. -2 ,0.857W cm -2 ,0.612W cm -2 . BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is the XRD spectrum of BGPC powder at room temperature;

[0026] Figure 2 This is the XPS fitting result diagram of Co element in BGPC powder;

[0027] Figure 3 The conductivity graph of BGPC powder tested at 25℃ intervals in the range of 400-850℃ in air atmosphere;

[0028] Figure 4 This is the thermogravimetric test curve of BGPC powder in air atmosphere;

[0029] Figure 5 The BGPC|LSGM|BGPC symmetric cell was heated in the temperature range of 600-800℃ at 100 mL min -1 Impedance tested at dry air flow rate of 100 mL min-1 at 700-800 °C for a symmetrical battery -1 (b) Impedance of a symmetrical battery tested at a dry air flow rate of 100 mL min in the temperature range of 600-650 °C. -1 Impedance tested at dry air flow rate;

[0030] Figure 6 The activation energy curve calculated from the impedance spectrum of the BGPC|LSGM|BGPC symmetric cell in the temperature range of 600-800℃;

[0031] Figure 7For the BGP C|LSGM|BGPC symmetric cell at 750℃ with 100mL min -1 100h impedance stability tested under dry air flow rate;

[0032] Figure 8 Output power test of Ni-GDC|LDC|LSGM|BGPC single cell in the temperature range of 700-800℃;

[0033] Fig. 9 The single cell (Ni-GDC|LDC|LSGM|BGPC) prepared with BGPC as cathode was heated at 700℃ with a charge of 0.5Acm -2 The stability test curve for 75h with a current density of ;

[0034] Fig.10 These are cross-sectional SEM images of the Ni-GDC|LDC|LSGM|BGPC single cell after stability testing; (a) is a cross-sectional SEM image of the BGPC cathode and LSGM electrolyte after the single cell test, and (b) is a cross-sectional SEM image of the Ni-GDC anode, LDC transition layer and LSGM electrolyte after the single cell test. DETAILED DESCRIPTION

[0035] The present invention is further described in detail below in conjunction with specific examples, but the embodiments of the present invention are not limited thereto.

[0036] Example 1

[0037] This embodiment provides a stable solid oxide fuel cell cathode material Ba realized by A-position regulation. 0.8 G 0.8 Pr 0.4 Co2O 6-δ The preparation method specifically comprises the following steps:

[0038] 1) Weigh 4.182 g of barium nitrate, 7.222 g of gadolinium nitrate, 3.480 g of praseodymium nitrate, and 11.641 g of cobalt nitrate, and add deionized water to completely dissolve them; weigh 4.504 g of glycine and 12.608 g of citric acid monohydrate as complexing agents according to the molar ratio of metal ions (Ba, Gd, Pr and Co): glycine: citric acid monohydrate of 4:3:3, and add them to the above solution to obtain a mixed solution;

[0039] 2) The mixed solution is heated and stirred at a constant temperature of 120° C. until the water evaporates to form a gel-like substance;

[0040] 3) placing the gel-like substance in an oven and heating it at 300° C. until it is completely burned, and keeping the temperature for 5 hours to obtain a fluffy cathode material precursor powder;

[0041] 4) The precursor powder was placed in a muffle furnace and calcined at 1000° C. for 5 h to obtain the desired cathode powder (denoted as BGPC).

[0042] Example 2

[0043] This embodiment provides a method of using Ba 0.8 G 0.8 Pr 0.4 Co2O 6-δ A symmetrical battery is prepared for the battery cathode. The symmetrical battery adopts a "cathode|electrolyte|cathode" structure, which specifically includes the following steps:

[0044] 1) Weigh 1 g of the cathode powder prepared in Example 1, and weigh 0.76 g of terpineol and 0.04 g of ethyl cellulose in a mortar at a mass ratio of powder: terpineol: ethyl cellulose of 100:76:4 to prepare a cathode slurry;

[0045] 2) Apply the cathode slurry evenly on the dense LSGM (La 0.8 Sr 0.2 Ga 0.8 Mg 0.2 O 3-δ ) on both sides of the electrolyte sheet, sintered at 1050 ° C for 2 h in an air atmosphere to form a layered double perovskite Ba 0.8 G 0.8 Pr 0.4 Co2O 6-δ Porous electrode, the effective cathode area of ​​the battery is 0.47cm 2 , a symmetrical battery is obtained; it is used for polarization impedance testing of cathode materials in the temperature range of 600-800°C. The polarization impedance of the battery at 800°C is 0.020Ωcm 2 .

[0046] Embodiment 3:

[0047] This embodiment provides a method of using Ba 0.8 G 0.8 Pr 0.4 Co2O 6-δ A single cell is prepared for the battery cathode. The single cell adopts a "Ni-GDC|LDC|LSGM|cathode" structure, which specifically includes the following steps:

[0048] 1) Weigh 1 g of the cathode powder prepared in Example 1, and weigh 0.76 g of terpineol and 0.04 g of ethyl cellulose in a mortar at a mass ratio of powder: terpineol: ethyl cellulose of 100:76:4 to prepare a cathode slurry;

[0049] 2) The cathode slurry was evenly brushed on the surface of the LSGM electrolyte and sintered at 1050 ° C for 2 h in an air atmosphere to form a layered double perovskite Ba 0.8 G 0.8 Pr 0.4 Co2O 6-δ Porous electrode, the effective cathode area of ​​the battery is 0.2826cm 2 ; A transition layer LDC is prepared on the other side of the electrolyte, and an anode Ni-GDC is prepared on the other side of the transition layer; it is used to test the output power of the cathode material in the temperature range of 700-800℃. The peak output power of the battery at 800℃ is 1.189W cm -2 .

[0050] Characterization results

[0051] (1) XRD characterization

[0052] Figure 1 BGPC (the cathode material Ba prepared in Example 1 0.8 G 0.8 Pr 0.4 Co2O 6-δ , abbreviated as BGPC) XRD spectrum at room temperature. It can be seen from the figure that the sample exhibits a good double perovskite phase.

[0053] (2) XPS characterization

[0054] Figure 2 The XPS fitting result of Co element in BGPC sample is shown in Figure 2. The Co 2p spectrum in the sample can be divided into three groups of peaks, corresponding to Co 4+ 、Co 3+ , Co4O3 satellite peaks, among which Co 4+ and Co 3+ The contents of Co and Co are 33% and 67% respectively. 4+ / Co 3+ small polarization pairs, which helps electron conduction.

[0055] (3) Conductivity characterization

[0056] Figure 3 The conductivity of BGPC was measured at 25°C intervals in the range of 400-850°C in air atmosphere. As can be seen from the figure, the conductivity of BGPC decreases with increasing temperature in the temperature range of 525-850°C, showing similar characteristics to other cobalt-based double perovskite materials. The conductivity of BGPC is 489-659S cm -1 The electrical conductivity meets the basic requirements of SOFC cathode.

[0057] (4) Thermogravimetric analysis

[0058] Figure 4 Thermogravimetric test curves of BGPC tested from room temperature to 1000°C in air atmosphere. The weight loss (~0.698%) from room temperature to 300°C may be attributed to the loss of adsorbed water and gas. The obvious weight loss (~1.899%) observed in the temperature range of 300-800°C is related to the loss of lattice oxygen, which is due to the thermal reduction of Co cations. At the medium operating temperature of SOFC, more weight loss means that more oxygen vacancies can be generated, which is expected to provide more ORR active centers and contribute to the high electrochemical performance of the BGPC cathode.

[0059] (5) Impedance and activation energy characterization

[0060] Figure 5 The BGPC|LSGM|BGPC symmetric cell (Example 2) was heated at 100 mL min in the temperature range of 600-800 °C. -1 Impedance tested at dry air flow rate of 100 mL min-1 at 700-800 °C for a symmetrical battery -1 (b) Impedance of a symmetrical battery tested at a dry air flow rate of 100 mL min in the temperature range of 600-650 °C. -1 The impedance tested under dry air flow rate. The polarization impedance at 800℃, 750℃, 700℃, 650℃, and 600℃ is 0.020Ωcm respectively. 2 ,0.037Ωcm 2 ,0.077Ωcm 2 ,0.185Ωcm 2 and 0.509Ωcm 2 .

[0061] Figure 6 The activation energy curve calculated from the impedance spectrum of the BGPC|LSGM|BGPC symmetric cell in the temperature range of 600-800°C. The activation energy of the BGPC cathode is 1.31 eV.

[0062] Figure 7 For the BGPC|LSGM|BGPC symmetric cell, the temperature was 750 °C and the flow rate was 100 mL min -1 The impedance stability of 100h tested under dry air flow rate. As can be seen from the figure, BGPC cathode material has good stability and is suitable as a cathode material for medium-temperature solid oxide fuel cells.

[0063] (6) Output power characterization

[0064] Figure 8The output power test of Ni-GDC|LDC|LSGM|BGPC single cell (Example 3) was conducted in the temperature range of 700-800°C. From the test results, it can be seen that the single cell with BGPC as cathode has an open circuit voltage of 1.078V, 1.084V, and 1.085V at 800°C, 750°C, and 700°C, respectively, and the output power can reach 1.189W cm -2 ,0.857W cm -2 ,0.612W cm -2 The electrochemical performance is significantly improved compared with traditional cobalt-based double perovskite materials.

[0065] Fig. 9 The Ni-GDC|LDC|LSGM|BGPC single cell (Example 3) was heated at 700°C with a current of 0.5Acm -2 The stability test was carried out for 75 hours at a current density of 1.37 W. From the test results, it can be seen that the single cell with BGPC as the cathode has not only a high output power at medium temperature, but also good stability, and is suitable as a cathode material for medium-temperature solid oxide fuel cells.

[0066] (7) SEM characterization

[0067] Fig.10 These are cross-sectional SEM images of the Ni-GDC|LDC|LSGM|BGPC single cell after stability testing; (a) is a cross-sectional SEM image of the BGPC cathode and LSGM electrolyte after the single cell test, and (b) is a cross-sectional SEM image of the Ni-GDC anode, LDC transition layer and LSGM electrolyte after the single cell test.

[0068] from Fig.10 It can be seen that after the test, the cathode and electrolyte interface are in close contact without shedding. BGPC has a good combination with the commonly used LSGM electrolyte, which is a prerequisite for single cells and symmetrical cells to have high electrochemical performance.

Claims

1. A stable solid oxide fuel cell cathode material achieved by A-position regulation, characterized in that: Its general formula is AA'B2O 6-δ The specific molecular formula is Ba 1-x G 0.8 Pr 0.2+x Co2O 6-δ , where 0 ≤δ ≤ 1, δ is the oxygen vacancy content; x = 0.2; The method for preparing a stable solid oxide fuel cell cathode material achieved by A-site regulation comprises the following steps: uniformly mixing Ba(NO3)2, Gd(NO3)3·6H2O, Pr(NO3)3·6H2O, and Co(NO3)2·6H2O in water according to the stoichiometric ratio of the molecular formula; adding glycine and citric acid monohydrate to form a mixed solution; heating and stirring at a constant temperature until the water evaporates to form a gel-like substance; heating the gel-like substance until it is completely burned to obtain a fluffy cathode material precursor powder; calcining the precursor powder to obtain the desired cathode material; the molar ratio of the total metal ions of Ba, Gd, Pr and Co: glycine: citric acid monohydrate is (3.5-4.5): (2.5-3.5): (2.5-3.5).

2. The method for preparing a stable solid oxide fuel cell cathode material by A-position regulation according to claim 1, characterized in that: The temperature of the constant temperature heating and stirring is 80-130°C; The gelatinous substance is heated to complete combustion means that the gelatinous substance is kept at 250-300°C for 5-10 hours; The calcination temperature is 900-1000°C, and the calcination time is 2-5 h.

3. The application of the stable solid oxide fuel cell cathode material realized by A position regulation according to claim 1 in a fuel cell is characterized in that: The stable solid oxide fuel cell cathode material achieved by A-site regulation is used to prepare the cathode in the oxygen ion conducting solid oxide fuel cell; The oxygen ion conducting solid oxide fuel cell comprises, from bottom to top, an anode, a transition layer, an electrolyte, and a cathode; the cathode is prepared from a stable solid oxide fuel cell cathode material achieved by A-position regulation; The electrolyte is La 0.8 Sr 0.2 Ga 0.8 Mg 0.2 O 3-δ ; The transition layer is La 0.4 Ce 0.6 O 2-δ ; The anode is NiO and Gd 0.1 Ce 0.9 O 2-δ Compound obtained.